2012
DOI: 10.4103/0976-237x.101081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two bleaching agents on the phosphate concentration of the enamel evaluated by Raman spectroscopy: An ex vivo study

Abstract: Aim:The aim of this ex vivo study was to evaluate the effect of in-office bleaching agents,–35% and 38% hydrogen peroxide containing bleaching agents, on the phosphate concentration of the enamel evaluated by Raman spectroscopy.Materials and Methods:Forty noncarious, craze-free human maxillary incisors, extracted for periodontal reasons, were used in this study. Baseline Raman spectra from each specimen were obtained before the application of the bleaching agent to assess the phosphate content present in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 4 publications
0
12
0
3
Order By: Relevance
“…In the present study, the roles of bicarbonate during demineralization and remineralization processes were analyzed using micro‐Raman (Raman) spectroscopy, a non‐destructive vibrational spectroscopic technique that permits investigation of organic and mineral species at micron resolution . Additional analyses were performed using transverse microradiography (TMR), which is the gold standard for analyzing longitudinal mineral distributions in subsurface lesions .…”
mentioning
confidence: 99%
“…In the present study, the roles of bicarbonate during demineralization and remineralization processes were analyzed using micro‐Raman (Raman) spectroscopy, a non‐destructive vibrational spectroscopic technique that permits investigation of organic and mineral species at micron resolution . Additional analyses were performed using transverse microradiography (TMR), which is the gold standard for analyzing longitudinal mineral distributions in subsurface lesions .…”
mentioning
confidence: 99%
“…Microporosity and enamel roughness can also increase when using higher concentration of peroxide, this has been proven by Berger's research with using H2O2 35% bleaching material and can cause the mineral content of Ca and P to reduce greater as when compared to using H2O2 10% bleaching material. 14 Decrease of Ca and P elements was also found in the results of the study by Syafriadi and Noh (2014), which showed calcium solubility as many as 1.016 ppm was found in the control Group and as many as 2, 607 ppm was found in the 10% hydrogen peroxide Group by using atomic absorption spectrophotometry. 8 Venkatesan et al (2012) also found Raman spectroscopy in their study that phosphate elements before bleaching showed mean and standard deviation value as 975.69 ± 4.52 and after bleaching with H2O2 38% showed mean and standard deviation value as 817.43 ± 12.96.…”
mentioning
confidence: 61%
“…14 Decrease of Ca and P elements was also found in the results of the study by Syafriadi and Noh (2014), which showed calcium solubility as many as 1.016 ppm was found in the control Group and as many as 2, 607 ppm was found in the 10% hydrogen peroxide Group by using atomic absorption spectrophotometry. 8 Venkatesan et al (2012) also found Raman spectroscopy in their study that phosphate elements before bleaching showed mean and standard deviation value as 975.69 ± 4.52 and after bleaching with H2O2 38% showed mean and standard deviation value as 817.43 ± 12.96. 14 Gopinath et al (2013) in his study found a decreased effect on enamel morphology by adding sweet potato extract into bleaching material namely H2O2 of 10% and 35% concentration, as compared to bleaching materials without sweet potato extract.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…1 Although bleaching agents have been shown to be effective treatment as regards color change, the residual oxygen remained on tooth after treatment has adverse effects on the bond strength. 2,3 Changes caused on the enamel surface may alter microhardness, surface roughness and morphology of the enamel, 4 loss of calcium and phosphate, 5,6 and lead to changes in the bond strength, when teeth are restored in the same session that bleaching is performed. 2,3 The literature has suggested that the professional should wait from 7 7,8 to 14 9 days after concluding the bleaching procedure to perform restorations.…”
Section: Introductionmentioning
confidence: 99%